The symbolism of The Title in Lulwa Al Mansouri’s stories - Alhammadi, Mariam; Alhashemi, Badeeah (Al-Adab Journal, 2024)
Textual thresholds are divided into two main parts: the surrounding text, which revolves around the written text or book, and the subsequent text, under which all texts outside the book, produced by the author related to his book, fall. The threshold of the title is one of the most important surrounding textual thresholds that the recipient faces when reading a narrative text, as he remains reminded of it and represents its content and main idea in the narrative and semantic path of the entire story. Semiotics has paid great attention to this threshold, as it is the most important key to the text and exploring its depths, as it is entrusted with three basic functions: the designating function, the suggestive semantic function, and the seductive function. This study seeks to analyze the symbolism of the threshold of the title, and to reveal its various functions in the narrative productions of the Emirati writer Lulwah Al Mansouri, in her three collections, which are: (A Grave Under My Head), (The Village That Sleeps in My Pocket), and (When the Earth Was Square). This is done by reading the titles at two levels: the level of linguistic and syntactic structure, and the intertextual level, with the aim of revealing how this threshold establishes independent connotations specific to its linguistic structure on the one hand, and other connotations in its relationship to the text on the other hand, and searching for the forms of these relationships, and how they can The title - summarized at the level of linguistic structure - has the fulfillment of these semantic relationships, and the extent to which the recipient can reveal that the title achieves connotations that overlap with the contents and purposes of the text, and how the circle of significance of the title expands until it enters into intertextual relationships with other texts. Accordingly, the study uses the semiotic approach to achieve these goals.